Motivations and barriers for corporate social responsibility reporting: Evidence from the airline industry. (October 2016) - Kuo, Tsai Chi; Kremer, Gül E. Okudan; Phuong, Nguyen Thi; Hsu, Chia-Wei
Abstract: Corporate social responsibility (CSR) has become a popular topic, as related research saliently suggests that CSR reporting has positive impacts, including improving corporate reputation, achieving employee trust, and enhancing customers' satisfaction. Consequently, in the past few years, companies have increasingly begun to report their CSR initiative outcomes, while the majority struggles to adopt similar initiatives. The research presented herein investigates motivations and barriers for reporting CSR outcomes by providing evidence from airline companies to investigate this disparity. Data collected through survey and confirmatory interviews indicates that respondents believe that government is the most important reader (or customer) of CSR reports. Similar to other industries, CSR reporting's major motivations are related to reputation and brand value, employees' CSR awareness, communication with stakeholders, management systems, management culture, market share, and transparency with the government. An enhanced understanding of related barriers and motivators should assist policymakers and company executives in their strategic decision-making regarding CSR reporting, thereby contributing to advancement toward sustainability. Highlights: This research focuses on investigating motivations and barriers for reporting on CSR outcomes by providing evidence from airlines companies. The barriers and motivators of CSR should inform policy makers and company executives during the stage of strategic decision-making. This research contributes advancement towards sustainability.